Evaluation and treatment of acne from infancy to preadolescence. Issue 6 (November 2013) - Admani, Shehla; Barrio, Victoria R.
Abstract Acne vulgaris is a common inflammatory skin condition affecting most individuals at some point during their lives. Although acne is more commonly seen in adolescents, it can be seen in younger patients as well. It can be useful to classify pediatric acne based on the age of presentation as infantile, mid‐childhood, or preadolescent. We describe a practical approach to the evaluation and treatment of acne in each of these age groups.